MOTIF ANGGOTA MENGIKUTI KOMUNITAS FACEBOOK PEKANBARU JUAL BELI ONLINE (PJBO) DI KOTA PEKANBARU - Ananda, Putri Rezki; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Community is a group of people who share the environment, attention, problem, and has an interest or the same passion for a topic, and can deepen their knowledge and skills by interacting continuously. In the community, members of which were in it has the intent, belief, resources, needs, risks, and a number of similar conditions. Unwittingly, the human community has been living in two worlds of life, that real life and public life virtual (cyber community). This virtual community of public life came to be known as a virtual community. The virtual community is a group of internet users who form a network of personal relationships. Pekanbaru Jual Beli Online (PJBO) included as one of the virtual community in the city of Pekanbaru which has a number of members of each semester increased dramatically. This study aims to determine the motive and communications experience Pekanbaru Jual Beli Online (PJBO) members in the city of Pekanbaru.This study uses qualitative research with phenomenological approach. Informants in this study were ten members are selected using purposive sampling technique. Data collection techniques is done through in-depth interviews, observation, and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed, the motive member following the facebook community Pekanbaru Jual Beli Online (PJBO) consists of because motive be able to trade online, try, selling a wider, more profit, sals easier, find items easily, get new relationships, and Pekanbaru Jual Beli Online (PJBO) is it marketplace Pekanbaru. While in the order to motive that wants their business and increasing widespread and one of them joined just for the money side only. Communication experiences are categorized into two pleasant communication experience in the form of their quick response from administrators when any members which in terms of buying and selling. While not pleasant communication experience in the form of their fraudulent thins done by one admin that makes its members at a disadvantage, being cheated at the time of purchase, and comparing prices with others.Keyword: virtual community, because motive, in order to motive, communication experiences